PENGARUH EFEK SAMPING TERHADAP PERILAKU KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI - Anas Tamsuri; Zauhani Kusnul; Aris Dwi Cahyono (JPK : Jurnal Penelitian Kesehatan, 2026)
Anemia is one of the most common health problems in Indonesia, especially iron deficiency anemia. One of the efforts to prevent and treat anemia is by providing Iron Supplements. However, giving iron supplement has side effects for some people. The purpose of this study was to determine whether there was an influence of side effects on the decision to continue taking iron supplement in adolescent girls. This research method was cross-sectional. The study population was all high school students at school X in Kediri Regency, a total of 365 people. The research sample was 186 respondents. The sampling technique was simple random sampling. Data collection was carried out using a questionnaire, and data analysis was carried out using the Mantel Hanzel Common Odds Ratio Estimate. The results of data processing showed that 18.82% respondents experienced side effects such as nausea, vomiting, diarrhea, constipation and dizziness. Of the number of respondent who experienced side effects, 67.65% decided to continue taking iron supplement and 32.35% decided not to take iron supplement. The results of the statistical test showed that the group with moderate side effects had a risk of stopping taking iron supplement 8.25 times greater than those with mild side effects. The statistical test also showed that the group with complex side effects had a risk of stopping taking iron supplement 2.5 times greater than those with side effects that were only one symptom. The results of the test showed that the results could not be generalized to a larger population. From this study, it is recommended to perform research with a larger sample size.